PERANCANGAN WEBSITE SMART SCHOOL SYSTEM SEBAGAI MEDIA INFORMASI DAN KOMUNIKASI DIGITAL DI SDN DANUKUSUMAN - Putra Setiawan, Praditia; Trisiana, Anita; Pandu Widhoyoko, Yudhistiro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to design and develop the Smart School System website portal at SDN Danukusuman Surakarta as a centralized, structured, and dynamic digital information and communication medium. The research method used is Research and Development (R&D), applying the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The system was built independently using the PHP Native programming language, a MySQL database integrated through XAMPP, and was supported by Unified Modeling Language (UML) blueprints and the Bootstrap framework to produce a responsive interface. The results of the technical feasibility testing using Black Box Testing through a questionnaire instrument assessment by three media expert lecturers obtained an average percentage of 92%, qualifying as